Chapter Rappresentazione, costruzione e visualizzazione di risorse terminologiche diacroniche nell'era del web semantico - Abrate, Matteo (Proceedings e report, 2021)
This article introduces the model DIATERM, devoted to representing the diachronic evolution of concepts and terms in a given domain, according to Semantic Web standards and Linked Data technologies. The approach adopted for the representation of temporal information is based on the reification of N-ary relationships. DIATERM is articulated on three levels, textual, terminological and conceptual. Each level can be affected, more or less simultaneously, by change. The use of SWRL rules allows to automatically assign temporal information, thus facilitating the construction of the terminological resource and highlighting any inconsistencies. Two examples of interrogation and visualization of diachronic terminological resources will be illustrated. The first example is taken from the resource dedicated to the astronomical terminology introduced by Christopher Clavius in his Commentary on the Sacrobosco's Tractatus de Sphaera. The second example is taken from the electronic lexicon of Ferdinand de Saussure's linguistic terminology.